Combined Method of Homicide-A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
It is one of the prime duties of the Forensic Pathologist to decide upon the cause of death in all unnatural deaths including homicidal deaths and it becomes very crucial when more than one method have been employed to kill the victim in homicidal deaths. It is very important to decide whether all the methods used were fatal or one among them is fatal and other methods contributing or hastening the death which plays an important role in the court of law while deciding as to the role of multiple offenders involved in the act. Hence the present case of ligature strangulation with stab injury to the abdomen is being discussed in the light of available literature.
Keywords: homicide; methods; cause of death